DETERMINAN PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2014-2017 - Lutviyani Indasah, 15.05.52.0248; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This research aims to analyze the influence of GDP, Population, investment, number of tourists visit, and the amount of the original Revenue toward Regional District/Town in Central Java province. Types of data used is secondary data. The population of this research constitutes the entire dala district/town in Central Java province. Sampling techniques using the census. Test engineering data using linear bergarnda analysis. The results of this research show that the GDP and the number of Companies has no effect against the original Revenue areas. Population, investment, and the number of tourists visit the positive effect significantly to Revenue of the original area.